USE OF MODERN INFORMATION TECHNOLOGY IN MICROBIOLOGICAL LABORATORY - Olszewska, Dominika Helena; Prauzner, Tomasz; Krupa, Piotr; Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In today’s world, the utilisation of modern information technology is becoming increasingly common in educational process – not only at primary and secondary school level, but most of all, at university level. The present article is a proposition of the implementation of information technology as a complement of microbiological laboratories. These classes are, most of all, practical, so a tweak of programs and simulations forms a prominent challenge for an academic. A student, who participates in laboratories, achieves specified abilities, however, he or she does not always have an opportunity to preserve them. In the thesis, there is presented a proposition of innovations, implemented into the educational process, which are a result of a long-time educational practice in terms of educating on the university level. Inasmuch as a complex process of teaching and learning (complete with concurrent components, which qualify its didactic effectiveness) is a subject matter of general didactics, the utilisation of information technology may form an excellent complement of laboratories. The utilisation of such solutions helps students to preserve the practical skills, which they acquire in laboratories. The emphasis is on simulation programs, and the open-source learning management system Moodle, which are considered as educational tools which have a relevant impact on the tenor of learner’s cognitive processing. Taking into consideration the advantages of these tools, and the commonness of modern information technology, the authors indicated a large universality of this medium, and its usefulness in the problem and empirical teaching. The presented group of software may bring a significant contribution to the development, the desirability, and the increase of absorption in vocational training. The ponderations are based on the basis of the cognitive theory and the idea of constructive education.